Indigenous Knowledge and Public Welfare: Insights from Rural Nepal - Tripathi, R.N. (Samsad Journal संसद जर्नल, 2025)
This paper offers a sociological examination of the intersections between indigenous knowledge systems and public welfare practices in rural Nepal. Challenging the hegemony of state-centred and Eurocentric development paradigms, it argues for the inclusion of alternative epistemologies embedded in the lived experiences of Nepal’s indigenous communities. Drawing upon communitarianism, post-development theory, and the concept of epistemologies of the South, the study highlights how collective action, mutual aid, and traditional ecological knowledge contribute substantively to localized welfare mechanisms. Case studies from Magar, Newar, Sherpa, and Tharu communities illustrate how these systems function as forms of embedded welfare institutions. The paper concludes by advocating for epistemic justice and participatory governance in welfare policy discourse.